2017
DOI: 10.1136/practneurol-2017-001609
|View full text |Cite
|
Sign up to set email alerts
|

Acute segmental poliomyelitis-like flaccid paralysis in an adult in the UK, associated with enterovirus D68

Abstract: Enterovirus D68 has been associated with a poliomyelitis-like illness, notably during an outbreak in 2014, and particularly affecting children in the USA. We report a case of acute segmental flaccid paralysis with respiratory involvement in an adult in the UK, with enterovirus D68 detected in a sputum sample. MR imaging of cervical spinal cord showed a longitudinally extensive T2 hyperintensity in the anterior cord. Cerebrospinal fluid showed an elevated white cell count, predominantly lymphocytic, with otherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Adding to the confusion is the restriction of the AFM case definition to individuals younger than 21 years of age, as it is currently understood that AFM does occur in adults as well. Although mostly children with a chronic illness were affected, children and adults without any known underlying condition were also reported ( Williams et al, 2016 ; Stacpoole et al, 2017 ). Additionally, it must be updated in accordance with increased data gained from reports.…”
Section: Ev-d68 Association With Acute Flaccid Myelitis (Afm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Adding to the confusion is the restriction of the AFM case definition to individuals younger than 21 years of age, as it is currently understood that AFM does occur in adults as well. Although mostly children with a chronic illness were affected, children and adults without any known underlying condition were also reported ( Williams et al, 2016 ; Stacpoole et al, 2017 ). Additionally, it must be updated in accordance with increased data gained from reports.…”
Section: Ev-d68 Association With Acute Flaccid Myelitis (Afm)mentioning
confidence: 99%
“…Simultaneously, similar upsurges were described by groups in Norway, Denmark, Germany, France, Spain, Portugal, Sweden, Wales (United Kingdom), Scotland (United Kingdom) and in the United States ( Dyrdak et al, 2016 ; ECDC, 2016 ; Wang et al, 2017 ). In addition, cases of EV-D68 were also linked with AFM in Wales (2 cases), Scotland (5 cases), England (1 case), Sweden (3 cases), Italy (2 cases), Spain (3 cases), France (at least 1) and Argentina (15 cases) with strains clustering with a divergent B3 lineage ( Antona et al, 2016 ; Dyrdak et al, 2016 , ECDC, 2016 ; PAHO/WHO, 2016 ; Williams et al, 2016 ; Cabrerizo et al, 2017 ; Esposito et al, 2017 ; Giombini et al, 2017 ; Kirolos et al, 2017 ; Stacpoole et al, 2017 ). A subsequent surveillance study ( Knoester et al, 2018 ) presented the results of a survey which found a total of 29 cases reported of EV-D68 infections associated with AFM in Europe in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…While polioviruses and other nonpoliovirus enteroviruses are recognized causes of AFM, this was the first time that EV-D68 had been widely associated with the condition. Another 144 confirmed cases of EV-D68-associated AFM occurred in the United States in 2016 [18,[21][22][23], and additional cases have been reported all over the world [24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…Viruses including non-polio enteroviruses (D68 and 71) and West Nile virus can involve anterior horn cells, causing segmental, asymmetric weakness potentially involving respiratory muscles. Throat swabs for enterovirus PCR and anti-West Nile virus IgM in CSF confirm the diagnosis 24 25…”
Section: Introductionmentioning
confidence: 94%